An Exploration of the Relation between Huta and Onan across the Batak Toba Settlements - Kevin Senjaya, William; Karyadi Kusliansjah, Yohanes; Rosaline Tobing, Rumiati (MAJ - Malaysia Architectural Journal, 2023)
Architecture is a space formed in a certain place, and is the result of the interaction between human culture and its natural environment. This culture is born from the principles or philosophies of the local community. As a "traditional" society, these principles or philosophies will not be separated from the surrounding nature, always based on the context of the place. The various principles or philosophies then give birth to various systems that must be carried out. In Batak Toba, the manifestation in the scope of architecture is the creation of spaces born from the system of society, kinship, belief, and so on. Indirectly, the various systems that give birth to the space will shape how social interactions between communities. Social interactions that occur can be in the form of relationships between individuals, between kinship groups, and or between villages. The Toba community recognizes the term huta-horja-bius. Huta is the smallest unit of bius inhabited by a small group of people who are intertwined with kinship between the king’s clan and boru. Interactions that occur in the huta are relationships between individuals and between kinship groups. In Batak Toba culture, there is a term onan function, which is a place where economic, social, and legal functions occur, and in onan there is also social and economic traffic with the outside world. The purpose of this research is to identify each spatial relationship based on the interactions that arise, namely in the huta of Tomok Parsaoran Village as well as the public space along the lake that is suspected of being onan, and to find out whether the public space is the place where inter-huta interactions occur. This research is part of a long and ongoing research and is based on qualitative methods with descriptive, and analytical approaches. The analytical part is divided into a description of the findings and discussion results that identify each space based on the real situation.